STRATEGI ADAPTASI PETANI KELAPA DI DESA LELILEF KECAMATAN WEDA TENGAH KABUPATEN HALMAHERA TENGAH - Iksan, Awaluddin; Deeng, Djefry; Sandiah, Nasrun (Universitas Sam Ratulangi, 2018)
In sustaining human life adaptation strategies need to adjust towards the natural environment as well as efforts in meeting the necessities of life. As an agricultural country, Indonesia has huge natural resources, one of which was plant the coconut (cocos nucifera) Palm plant, where the added value which are exploited by the community, can be processed into coconut oil, food and cosmetic ingredients.The villagers live a little Lelilef who opt into the coconut farmers. Some residents prefer the work of others, such as merchants, opened food stalls, shops. Some choose to become miners. It is this opportunity that is viewed by society, they decided to look for another job with the expectation of earning and a better life. But with low skills and education, then a job in the formal sector are difficult to obtain. Be a coconut farmer is a realistic option, however promising, because before the presence of the mines, the community in the village of Lelilef mostly work as farmers. The limitations education makes them have to choose farmed, and became a coconut farmers as the main livelihood for the coconut farmers as has been pursued since ancient compared the work of the other.They adapt and still survived as the coconut farmers is due to the strong emotional bond with the land, land is the root of the formation socio-cultural character of coconut farmers. If the coconut farmers separated from the land will affect his life.Keywords: adaptation, plant, coconut